The Influence of Price Perceptions, Service Quality and Trust on Gojek Customer Loyalty at the Universitas Sumatera Utara - Endang Lestari; Arlina Nurbaity Lubis; Beby Karina Fawzeea Sembiring (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to analyze the influence of price perceptions, service quality and trust on Gojek Customer Loyalty at the University of North Sumatra. The object of this research is Gojek users at the University of North Sumatra. The sampling technique uses non-probability sampling, the Convenience Sampling method. The number of samples used in this research was 218 respondents. The analytical method used in this research is a multiple linear regression model. The research results show that price perception has a positive and significant effect on Gojek Customer Loyalty at the University of North Sumatra. Service quality has a negative and insignificant effect on Gojek Customer Loyalty at the University of North Sumatra. Trust has a positive and significant effect on Gojek Customer Loyalty at the University of North Sumatra.